The Case of the Congenital Cataract Development in a Child with Kabuki’s Makeup Syndrome - T. B. Kruglova; N. S. Egiyan (Oftalʹmologiâ)
Kabuki makeup syndrome is a rare genetic disease. The features of the child’s face resemble the mask of the actors of the Japanese Kabuki theater. Accompanied by multiple anomalies of various organs and systems. Cases of congenital cataract (CC) are not described. Purpose: to describe a clinical case of diagnosis and treatment of congenital cataracts in a child with Kabuki syndrome.Material and methods. Child M.,15 years old with syndrome Kabuki make-up. At OD — zonular congenital cataract in 1-degree of turbidity, OS — zonular congenital cataract 3rd degree of turbidity Conducted a survey and phacoaspiration with IOL implantation HOYA 24,0 D at OS. Results. Visual acuity: OD = 0.6 s –1.0 D = 0.8–0.9; OS before surgery = 0.02 n/c, after surgery = 0.05 n/c (amblyopia obscuration). Lens OD-opacity disc, through which the Central parts of the fundus can be investiture with Ophthalmoscope. Lens OS-atypical disk with uneven opacity in the form of dark and light bands, the Central parts of the fundus can’t be investigated with ophthalmoscope, viewed only peripheral vessels. Ultrasound examination OU: single floating opacities in vitreous body, APA of eye = 22.7 mm. Electrophysiological examination-reduction of a number of indicators OS. Resume. 1. In children with the syndrome Kabuki make-up can be congenital zonular cataracts. 2. Taking into account the progressive nature of lens opacity, a dynamic examination with a wide pupil is necessary for timely referral to surgical treatment. 3. There is a risk of developing exudative proliferative reactions in the early postoperative period.